Comparison of Maladaptive Meta Cognition Beliefs among Substance Dependents and Non-Dependents - Omid Saed; Hamid Yagobi; Rasoul Roshan; Marzyeh Soltani (Drug Control Headquarters, Research and Education Office, 2011)
Introduction: The aim of present research was the comparison of maladaptive meta cognition beliefs among substance abusers and non abusers. Methods: For this purpose 70 substance abusers and 70 individuals from the general population by purposive sampling participated in this research and responded to meta cognition questionnaire. For analysis data multiple analysis of variance (MANOVA) and discriminant analysis were run. Results: MANOVA revealed that there was significant difference in linier combination of dependent variables (meta cognitive beliefs) among two groups also, analysis of dependent variables lonely showed that two groups were significantly different in Positive meta cognitive beliefs, "Negative meta cognitive beliefs", "lack of cognitive confidence", "need to control of thoughts", and "cognitive self-consciousness". Also, the discriminant analysis indicated that three meta-cognitive factors included "negative meta cognitive beliefs", "need to control of thoughts" and "cognitive self-consciousness" were significant predictors to discriminate substance abusers. Conclusion: With consideration of the results it can be concluded that substance abusers have more maladaptive beliefs and these maladaptive beliefs can lead to susceptibility toward substance abuse and staying in this disorder. It is hoped that psychotherapists can be more useful in treating and staying in this research.